2006
DOI: 10.1007/s00125-006-0267-7
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum resistin in elite endurance athletes with high insulin sensitivity

Abstract: Aims/hypothesis: Resistin is an adipokine associated with obesity and type 2 diabetes in animal models, but in humans its role remains uncertain. This study was undertaken to test whether serum resistin is related to insulin resistance and markers of low-grade inflammation in elite athletes taken as a model of extreme insulin sensitivity. Subjects materials and methods: In 23 elite athletes (sprinters, middle-distance and marathon runners) and in 72 sedentary men including lean and obese individuals with NGT, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 35 publications
3
21
2
Order By: Relevance
“…In the baseline phase analysis of this study we didn't detect any significant differences in serum levels of adiponectin at baseline between trained and untrained individual. These finding confirmed those of Varady et al [13] who didn't detect significant differences in plasma adiponectin between trained and sedentary subjects at baseline and those of Perseghin et al who didn't detect any differences in plasma adiponectin [14] between marathon runner and lean sedentary individual matched for BMI. A novel finding of this study was that, the basic level of RBP4 and CRP also didn't differ between trained and untrained groups.…”
Section: Discussionsupporting
confidence: 88%
“…In the baseline phase analysis of this study we didn't detect any significant differences in serum levels of adiponectin at baseline between trained and untrained individual. These finding confirmed those of Varady et al [13] who didn't detect significant differences in plasma adiponectin between trained and sedentary subjects at baseline and those of Perseghin et al who didn't detect any differences in plasma adiponectin [14] between marathon runner and lean sedentary individual matched for BMI. A novel finding of this study was that, the basic level of RBP4 and CRP also didn't differ between trained and untrained groups.…”
Section: Discussionsupporting
confidence: 88%
“…Because all of the subjects in the current study began with healthy fasting levels of both insulin and glucose, it is unlikely that increasing exercise could suppress these concentrations further. The exercise group's QUICKI values were similar to those reported for elite athletes with high insulin sensitivity [23]. Indeed, lower concentrations of glucose in the fasting state may even be considered a negative adaptation because it could lead to fasting hypoglycemia.…”
Section: Discussionsupporting
confidence: 74%
“…After exercise they ranged from 8.1±1.55 to 9.6±3.06 ng/ml (Table 5) Ostrowski et al (1999), showed that intense physical exercise induces a 2 to 3 fold increase in TNF-α and IL-1β levels, while Pedersen and Hoffman-Goetz (2000) revealed that it may modulate dramatic increases in IL-6 levels. ng/ml in our study, whereas Perseghin et al (2006) claimed a mean value of 4.5±1.6 ng/ml in elite runners. Although one original article claimed that there was an association between resistin concentration and insulin resistance in obese rodents (Steppan et al, 2001), further studies by Perseghin et al (2006) (Aslan et al, 1998;Goto et al, 2003).…”
Section: Discussioncontrasting
confidence: 65%
“…ng/ml in our study, whereas Perseghin et al (2006) claimed a mean value of 4.5±1.6 ng/ml in elite runners. Although one original article claimed that there was an association between resistin concentration and insulin resistance in obese rodents (Steppan et al, 2001), further studies by Perseghin et al (2006) (Aslan et al, 1998;Goto et al, 2003). In the current study, TBARS concentration (D=34.57%) (Szcześniak et al, 1998).…”
Section: Discussioncontrasting
confidence: 65%